Sustainable transformation of Romanian companies through industry 4.0, green production and environment commitment - Georgeta-Mădălina Meghișan-Toma; Silvia Puiu; Nicoleta Florea; Flaviu Meghișan; Roxana Bădîrcea; Alina Manta (Amfiteatru Economic Journal, 2022)
The main aim of this research article is to develop an econometric model in order to establish the influence of green performance on digitization, green production and environment commitment. The data was collected through a questionnaire- based survey on companies' representatives. The analysis was made using the Partial Least Square - Structural Equation Modelling (PLS-SEM) with the statistical software SmartPLS. The results of the research confirm the three hypotheses. Thus, green performance of Romanian companies has a positive impact on green production, digitization and environment commitment. The novelty consists in the interconnected analysis of the four variables (green performance, digitization, green production and environment commitment), the research highlighting valuable results that can be used by the companies to improve their green performance, using green production and digitization. The paper offers a picture of the sustainable transformation of Romanian companies based on the industry 4.0, green production and environment commitment, highlighting the interdependence of the analysed variables. The research is helpful for companies that want to be more responsible towards the environment and the community.
Keywords: M10; M12; M13; M14; M15; M21; 330; digitization; sustainability; environment commitment; greenp erformance; green production; industry 4.0